A Study on the Social Problems Faced by the Descendants of the Refugees of Dhubulia Refugees-Camp for Getting Education - Arup Biswas , Prof. R Balakrishnan (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
The refugees undoubtedly suffer a great deal of hardship and trauma and they also show tremendous determination to make the best of a bad situation and to prepare for the day when they can resume a normal way of life. This determination is to be seen most clearly in the very high value which refugees place on all forms of education. Indeed, experience shows that once refugees have met their basic need for food, water and shelter, their primary concern is to ensure that their children can go to school. Tragically, the international community has tended to place less value on education than refugees themselves. With humanitarian needs growing in many parts of the world, the funding available for refugee assistance program has become progressively tighter. In many situations, this has meant that the resources available for education have declined. It is impossible to calculate the immense costs that are incurred by depriving refugees of education. A refugee who goes without education cannot look forward to a more productive and prosperous future. A refugee who is unable to attend school or a vocational training course is more likely to become frustrated and involved in illegitimate or military activities. A refugee who remains illiterate and inarticulate will be at a serious disadvantage in defending his or her human rights. The education of refugees is an important but neglected humanitarian issue.Education provides opportunities for students, their families and communities to begin the trauma healing process, and to learn the skills and values needed for a more peaceful future and better governance at local and national levels.Now, it is very much relevant and equally important, the problems of the descendants of refugeein getting education. There are so many different kinds of problems faced by them whether it is problems in school regarding teachers, regarding understanding or about the family problems or other social problems. Struggling with all these odds, the descendants of the refugee are to get education and get development. This study will explore the social problems faced by the descendants of the refugee in the way of getting education.